A New anticipatory speed-controller for IC engines based on torque sensing loop - Ali, Abdul baki Khalaf; kheioon, Imad abdul-kadhem; Ali, Mushtaq Kadhim (Iraqi Journal for Electrical and Electronic Engineering, 2010)
Some engineering applications requires constant engine speed such as power generators, production lines ..etc. The current paper focuses on adding a new closed loop based on engine torque. Load cells can be used to measure the torque of load applied , the electrical signal is properly handled to manipulate a special fuel actuator to compensate for the reduction in engine speed. The speed loop still acts as the most outer closed loop. This method leads to rapid speed compensation and lead control action.